2022
DOI: 10.1002/qj.4398
|View full text |Cite
|
Sign up to set email alerts
|

Role of land‐surface vegetation in the march of Indian monsoon onset isochrones in a coupled model

Abstract: Although the Climate Forecast System version‐2 model simulates an overall dry bias in boreal summer mean rainfall over Indian land, the deficiency is particularly prominent over northwest India. The prevailing dryness limits the interannual prediction skill of the Indian summer monsoon rainfall and its subseasonal variability because of poor representation of latent heating due to weak moist convection and the resulting circulation. Here, we show that land‐surface vegetation plays a crucial role in determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Saha et al (2014) gives a detailed description of the CFSv2 model. The version of CFSv2 employed here is similar to that used in Rajendran et al (2021) and Chakraborty et al (2023).…”
Section: Model Details and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saha et al (2014) gives a detailed description of the CFSv2 model. The version of CFSv2 employed here is similar to that used in Rajendran et al (2021) and Chakraborty et al (2023).…”
Section: Model Details and Experimentsmentioning
confidence: 99%
“…Zhang et al (2021Zhang et al ( , 2022 have demonstrated that increasing the vegetation cover in the Loess Plateau in China leads to net increase in water yield. Chakraborty et al (2023) has shown that vegetation changes influence monsoon onset predictions by modulating moisture advection over Indian land. Further, Indian monsoon rainfall has declined due to the reduction in forest cover (Devaraju et al 2015, Paul et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Chakraborty et al . (2023) and Menon et al . (2022) showed that the specified soil and vegetation conditions can affect local onset by altering the time‐scales of soil moisture–precipitation feedback via the timing of diurnal convection.…”
Section: Introductionmentioning
confidence: 95%
“…One of the famous mechanisms was proposed by Eltahir (1998) and Seneviratne et al (2010): increased soil moisture affects the rainfall both by changing the Bowen ratio and the surface albedo, which together influence the moist static energy in the atmospheric boundary layer and the rainfall pattern over a region. Chakraborty et al (2023) and Menon et al (2022) showed that the specified soil and vegetation conditions can affect local onset by altering the time-scales of soil moisture-precipitation feedback via the timing of diurnal convection. In the context of these studies highlighting land-atmosphere feedback and land surface memory on a monthly scale, understanding the role of soil moisture initialization on the extended-range forecast is essential.…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact demonstrates significant spatial variability and could modulate seasonal rainfall as well. A recent study by Chakraborty et al (2022) showed that a realistic distribution of land surface vegetation could improve the forecast of the northwestward progress of the onset of the Indian summer monsoon due to improved subseasonal moisture flux and land-atmosphere interaction. Land surface processes thus influence various phases of the monsoon from onset to subseasonal phenomena.…”
mentioning
confidence: 99%